Flood Mapping by Using Hydrologic Engineering Center River Analysis System (HEC-RAS) in Kota Tinggi, Johor, Malaysia - Mustaffa, Mohammad Harith Bin; Abu Talib, Siti Hidayah (Recent Trends in Civil Engineering and Built Environment, 2022)
Flood disaster are a natural disaster which cause widespread destruction and loss of life. Flood is an overflow of water from water channel that submerges land. The target of this topic is to determine the probability that the flood could happen in Kota Tinggi, Johor, Malaysia. The main objective of the research is to produce the flood mapping on the Sungai Johor that flows along the town of Kota Tinggi. The choice of using HEC-RAS software is to prove that is suitable to use in flood mapping or flood plain process by simulating the potential flood area by using various hydrological data such as geometric data and flow data. The flood plain mapping is produced according to the ARI of 2, 10, 25, 50 years with a discharge of 6084 (m^3/s), 9850 (m^3/s), 11619 (m^3/s), and 13926 (m^3/s) respectively by using the HEC-RAS software is proven. The source and characteristic of flood in the town of Kota Tinggi is due to the river flood by the Sungai Johor that flows along the town. Along the 50 years flood simulation, the inundated area will increase in size compared to the simulated flood years before.